How artifacts afford the power and politics of everyday things - Davis, Jenny L.; Recorded Books, Inc. ([S.l.] : The MIT Press, 2020)
A conceptual update of affordance theory that introduces the mechanisms and conditions framework, providing a vocabulary and critical perspective. Technological affordances mediate between the features of a technology and the outcomes of engagement with that technology. The concept of affordances, which migrated from psychology to design with Donald Norman's influential 1988 book, The Design of Everyday Things, offers a useful analytical tool in technology studies--but, Jenny Davis argues in How Artifacts Afford, it is in need of a conceptual update. Davis provides just such an update, introducing the mechanisms and conditions framework, which offers both a vocabulary and necessary critical perspective for affordance analyses.
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Manufactures -- Psychological aspects; Product design -- Social aspects